The Role of Organizational Culture in Improving Employee Performance in The Era of Globalization - Ahmad Sahal Gojali; Anysha Rahmasuri; Eneng Selvi; Rahmi Rahmawati Sayyidah; Riyan Mirdan Faris; Kharisma; Bagja Rahma Putra (Future Science, 2020)
The purpose of this study is to determine how the Role of Organizational Culture in Improving Employee Performance in the Age of Globalization. This research is a type of descriptive qualitative research, namely research based on data that is then collected in the form of words and not in the form of numbers. Data collection is carried out in this study using secondary data techniques, which are generally secondary data in the form of documentation data or existing report data. From this study, the authors took from books and journals as secondary data. The research results indicate that it turns out that in improving employee performance one of the influences is the role of organizational culture. Having a culture in an organization will make its employees have the same perspective in carrying out their work activities because the organizational culture that exists in a company is a reflection of its employees. The existence of employees in an organization aims to change and develop the organization into an organization that can compete competitively in the era of globalization and can also make the organization superior. Amid globalization which is rapidly undergoing many unexpected and unpredictable changes, a leader must place himself following the demands of a global organization and have a strong leadership attitude. That way, foreign cultures that enter this era of globalization can be well accepted and instilled. by instilling global organizational values in the existing organizational culture and building good communication with employees to make these values a shared value. When leaders can make cultural values that are included in this era of globalization as shared values, employees will be familiar with cultural changes. So that their performance will not be disturbed, and even tend to increase.